2009
DOI: 10.5551/jat.e463
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Fenofibrate and Fish Oil in Relation to Lipid Metabolism in Mice

Abstract: Aim:The aim of our study is to elucidate the interactive effects on lipid metabolism of fenofibrate and two fish oils with EPA and DHA contents in mice. Methods: Female C57BL/6J mice were fed purified experimental diets containing safflower oil (SO), EPA-rich menhaden oil (MO) or DHA-rich tuna oil (TO) with or without 0.1% fenofibrate for 8 weeks. At the end of the experiments, we measured plasma lipids and hepatic triglycerides and cholesterol, and the hepatic mRNA expression of lipogenic and lipidolytic gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
2
19
1
Order By: Relevance
“…The results of the present experiment regarding rat liver Hmgcr gene (Figure 1) do not agree with the data found in mice, where Hmgcr gene expression was decreased by EPA/DHA (Arai et al 2009a), by menhaden oil (EPA) (Arai et al 2009b), by FO (Hirako et al 2010) or by EPA alone (Sugiyama et al 2008). On the other hand, only tuna oil (DHA), but not menhaden oil (EPA) decreased expression of Ldlr in the study of Arai et al (2009b).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The results of the present experiment regarding rat liver Hmgcr gene (Figure 1) do not agree with the data found in mice, where Hmgcr gene expression was decreased by EPA/DHA (Arai et al 2009a), by menhaden oil (EPA) (Arai et al 2009b), by FO (Hirako et al 2010) or by EPA alone (Sugiyama et al 2008). On the other hand, only tuna oil (DHA), but not menhaden oil (EPA) decreased expression of Ldlr in the study of Arai et al (2009b).…”
Section: Discussioncontrasting
confidence: 97%
“…On the other hand, both Arai et al (2009a) and Arai et al (2009b) reported a decrease of SREBP-2 mRNA in EPA/DHA-fed mice. Similarly, SREBP-1c and SREBP-1 mRNA decreased in the liver of the FO-fed rats (Takahashi 2011) and n-3 PUFA-fed rats (Lu et al 2011), respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous study also showed that fenofibrate treatment markedly increased plasma HDL-cholesterol in C57BL/6 mice 17) . The data presented here indicate that the increase of plasma total cholesterol in DHA FF fed mice is due to the increase of plasma HDL-cholesterol by the effect of fenofibrate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combination of EPA and DHA provided a stronger hypolipidemic effect than each alone 16) . In our previous study, consumption of different fish oils, specifically EPA-or DHA-rich fish oil, did not produce different effects on lipogenesis in C57BL/6J mice 17) . In this study, we decided to use KK mice that develop non-insulindependent diabetes mellitus with moderate obesity, insulin resistance and hyperlipidemia 18) .…”
Section: Introductionmentioning
confidence: 99%
“…Whether brain or circulating triacylglycerol levels are modifi ed by our dietary DHAenrichment regime remains to be explored. A longer period of DHA supplementation may be required, as suggested by the demonstration that -3-rich diets can lower plasma triacylglycerol (usually by 10-20%) in various strains of healthy mice but only after 4-16 weeks of supplemental -3 fatty acid intake (59)(60)(61).…”
Section: -3 -6 and -9 Metabolitesmentioning
confidence: 99%